Comics in ToonDoo and Collaborative learning, a visual literacy resource to evidence vocabulary learning with emphasis in action verbs in an EFL group of seventh graders in a Cajicà school (2016)
The objective of this paper is to determine how the implementation of visual literacy tools such as comics created through ToonDoo (digital tool) evidences in an EFL group of seventh graders at a Cajicà School to use vocabulary with emphasis in action verbs. This document explains an action research proposal with implementation. The process involved diagnostic tests in written and oral forms, a journal, visual literacy activities involving a comic design, an interview and rubrics for data collection. The methods for data analyzed were carried out by the Content Analysis Approach and the Narrative Approach. The results demonstrated that visual literacy tools such as comic created in ToonDoo evidence the use of vocabulary but in a very slow manner due to the complexity of learning the tool in function of the allotted time despite the substantial interaction of the students in the assigned project.